Intracranial and Intralabyrinthine Fluids Basic Aspects and Clinical Applications - Ernst, Arne; Marchbanks, Robert; Samii, Madjid (Springer Berlin Heidelberg, 1996)
This book provides an overview of current scientific knowledge on volume and pressure regulation as well as on basic neuroscientic aspects of liquor and labyrinthine space. Clinical and surgical concerns regarding diagnostics -such as non invasive pressure measurements methods- and therapy -such as neuroendoscopy and neuronavigation- are discussed
Keywords: Neurosurgery; Neurology; Otorhinolaryngology; Hirndruck; Perilymphe; Wechselwirkung; Otoneurologie; Endolymphe; Liquor cerebrospinalis; Hirndrucksteigerung; Konferenzschrift -- 1995 -- Seeheim Seeheim-Jugenheim; Konferenzschrift -- 1995 -- Seeheim-Jugenheim